Determination of Risk Factors Predisposing Chicken to Influenza A Virus Infection at Uasin Gishu County, Kenya - Carozone, S. N.; Ngeiywa , M.; Salinah, R. (Africa Environmental Review Journal, 2022)
Influenza A is a highly contagious virus of global health concern causing significant deaths in chicken. The virus is a threat to poultry production in many countries including Kenya, due to location along key wild bird’s migratory routes. This study aimed at determination of risk factors predisposing chicken to Influenza A virus infection in Uasin, Gishu County, Kenya. To achieve this, age, sex, breed (hybrid and indigenous), vaccination status (avian flu vaccine), restocking source, management systems of chicken and seasonal weather variations were assessed to determine those that are associated with virus infection. The study was conducted at the Regional veterinary investigation laboratories (RVIL) in Eldoret. Oropharyngeal swab were collected from 305 sampled chicken brought in by farmers to the laboratory from all the sub-counties of Uasin, Gishu County, Kenya for screening of suspected zoonotic diseases. Real-time reverse transcriptase polymerase chain reaction (rtRT-PCR) was used to diagnose the virus. Face to face interviews with farmers who brought their chicken for screening in the laboratory were conducted to gather information on possible confounding factors such as the sex, age, breed, management system of chicken, seasonal weather variation, restocking source and vaccination status of chicken which were recorded using a structured questionnaire. Pearson chi square technique was employed to test for statistical significance on differences across data sets at a 95% confidence level. The result showed that there was significant difference in influenza A virus infection positivity between hybrid and indigenous breeds (p = 0.000), while age (p-0.6992), sex (p-0.879), management systems (p-0.5747), vaccination status (p-0.81), restocking source (p-0.549) and seasonal weather variation (p-0.42) were not significantly associated with Influenza A virus in chicken. In conclusion breed of chicken demonstrated a statistically significant effect as a predisposing factor on the infection by Influenza A virus in chicken in Uasin, Gishu County, Kenya. The study recommends that public health veterinary sectors within the ministry of agriculture from the County should create awareness to farmers on the transmission, symptoms, control and treatment for Influenza A virus among hybrid and indigenous breeds of chicken.